2014
DOI: 10.1080/10824669.2014.954044
|View full text |Cite
|
Sign up to set email alerts
|

“I Am Not a Shelter!”: Stigma and Social Boundaries in Teachers’ Accounts of Students’ Experience in Separate “Sheltered” English Learner Classrooms

Abstract: This study investigates how teachers interact with immigrant-origin youth in school-based contexts of reception that mediate youth's educational opportunities. One understudied context is sheltered instruction, where English learners (ELs) are placed into separate content-area courses to target their linguistic needs. This qualitative study highlights the unintended consequences of ELs' placements by examining 3 teacher cases in depth. Teachers' accounts reveal that EL content courses designed to increase acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
80
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 41 publications
1
80
0
Order By: Relevance
“…Even in more progressive contexts, EL students are often placed in segregated content area classes, with teachers expected to provide modified instruction (Dabach, 2011). Many argue that secondary EL content area coursework covers less material and provides a watered-down curriculum (Callahan, 2005; Dabach, 2014; Ek, 2009). In addition, full integration of EL students, risk their placement with non-EL certified teachers unprepared to meet both their students’ linguistic and academic needs.…”
Section: Discussion and Conclusion: Implications For Policy And Practicementioning
confidence: 99%
“…Even in more progressive contexts, EL students are often placed in segregated content area classes, with teachers expected to provide modified instruction (Dabach, 2011). Many argue that secondary EL content area coursework covers less material and provides a watered-down curriculum (Callahan, 2005; Dabach, 2014; Ek, 2009). In addition, full integration of EL students, risk their placement with non-EL certified teachers unprepared to meet both their students’ linguistic and academic needs.…”
Section: Discussion and Conclusion: Implications For Policy And Practicementioning
confidence: 99%
“…Scholarship in EL education has continued to examine the linkages between a student's status as an English learner and curricular learning opportunities in schools (Callahan et al, 2010;Dabach, 2014;Umansky, 2016aUmansky, , 2016b. Embedded in the larger conceptual framework of opportunity to learn, these studies, among others, have illuminated the ways in which ELs have differential-specifically, much more limited-educational opportunities for learning than their monolingual English-speaking peers.…”
Section: Geospatial Inquirymentioning
confidence: 99%
“…Studies have shown that ELs are less likely to take critical content courses (Callahan & Shifrer, 2016), particularly science (Callahan, Wilkinson, & Muller, 2010;Umansky, 2016a). Second, even when ELs take content area courses, curricula are often watered down (Dabach, 2014;Valdés, 2001). Such findings indicate that a trade-off occurs in schools: Content learning is often forfeited for ELs because of second language (L2) learning needs (Kanno & Kangas, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The ability to engage with rigorous academic content is critical; however, educators often conflate English proficiency with academic prowess and limit EL students’ academic exposure while they learn English (Callahan, 2005; Dabach, 2014). Adding to the opportunity gap, too few teachers of EL students have been fully trained to meet their charges’ unique linguistic and educational needs (Gándara et al 2003; Samson & Collins, 2012).…”
Section: The El Opportunity Gap: Policy Instruction and Equitable Amentioning
confidence: 99%